2018
DOI: 10.1007/jhep10(2018)179
|View full text |Cite
|
Sign up to set email alerts
|

Finite deformations from a heterotic superpotential: holomorphic Chern-Simons and an L∞ algebra

Abstract: We consider finite deformations of the Hull-Strominger system. Starting from the heterotic superpotential, we identify complex coordinates on the off-shell parameter space. Expanding the superpotential around a supersymmetric vacuum leads to a third-order Maurer-Cartan equation that controls the moduli. The resulting complex effective action generalises that of both Kodaira-Spencer and holomorphic Chern-Simons theory. The supersymmetric locus of this action is described by an L 3 algebra. C The off-shell N = 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(83 citation statements)
references
References 91 publications
(227 reference statements)
2
81
0
Order By: Relevance
“…Another interesting direction is to view ∆W as an action which can be quantised. Indeed, the famous Donaldson-Thomas invariants of Calabi-Yau manifolds equipped with holomorphic sheaves can be interpreted as correlation functions within holomorphic Chern-Simons theory [1][2][3], and it has been suggested that similar invariants may be defined for the Hull-Strominger system using the corresponding superpotential [11]. Donaldson and Segal have suggested that similar invariants could be defined for G 2 manifolds [4], though it has been debated to what extent such invariants depend on the given G 2 structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting direction is to view ∆W as an action which can be quantised. Indeed, the famous Donaldson-Thomas invariants of Calabi-Yau manifolds equipped with holomorphic sheaves can be interpreted as correlation functions within holomorphic Chern-Simons theory [1][2][3], and it has been suggested that similar invariants may be defined for the Hull-Strominger system using the corresponding superpotential [11]. Donaldson and Segal have suggested that similar invariants could be defined for G 2 manifolds [4], though it has been debated to what extent such invariants depend on the given G 2 structure.…”
Section: Discussionmentioning
confidence: 99%
“…As required by N = 1 supersymmetry in four dimensions, it is a holomorphic functional on the off-shell parameter space of the system, and its critical locus corresponds to the infinitesimal moduli space. Adopting this perspective leads to an understanding of the structure of the finite deformations of these configurations, and the holomorphicity of the superpotential provides constraints enough to determine a third-order Maurer-Cartan equation for finite moduli [11].…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, it is natural to speculate that a generalised geometry based on this bundle could be a useful tool in studying these systems. In [], the finite deformations of the system were studied both as an interesting problem in their own right, and as a means to uncover the relevant generalised geometry of scriptQ.…”
Section: Heterotic Supergravity and Deformations Of N=1 Backgroundsmentioning
confidence: 99%
“…This is equivalent to a smoothly varying element of the homogeneous space SO(6,6)×R+SUfalse(3false)×SOfalse(6false)One can then perform a decomposition of the adjoint representation of prefixitalicSOfalse(6,6false)×double-struckR+ to identify complex coordinates on this space, which when allowed to vary smoothly over the manifold X provide us with complex coordinates on the space of structures. In [] it is argued that the relevant coordinates on the space of structures can be identified with μnormalΩ0,1false(Tfalse(1,0false)false) (which is i2ΔJ exactly as for the almost complex structure), and xnormalΩ1,1 and bnormalΩ0,2 which are the (1,1) and (0,2) parts of the holomorphic variation Δ(B+iω).…”
Section: Heterotic Supergravity and Deformations Of N=1 Backgroundsmentioning
confidence: 99%
“…See, e.g.,[6,7,8,9,10,11,12,13,14,15] for recent studies of heterotic strings 2. See, for example,[17,18,19,20,21] for recent studies on the stable degenerations in F-theory/heterotic duality.…”
mentioning
confidence: 99%